Biometric properties and selected chemical concentration of cauliflower influenced by wastewater applied through surface and subsurface drip irrigation system. (15th December 2016) - Tripathi, Vinod Kumar; Rajput, Thakur Bahadur Singh; Patel, Neelam
Abstract: The necessity of municipal wastewater reuse for irrigation has become imperative for water scarce countries. It is also supportive to limit the environmental pollution. Field experiment was conducted to investigate the biometric properties of the cauliflower crop and its chemical concentration. To limit the entry of heavy metal elements into the food chain, crop was irrigated through drip irrigation system with municipal wastewater. It was treated though three different type filtration processes viz., sand media type, disk type and combined sand media and disk type filters under surface and subsurface placement of drip laterals. Highest leaf area index and curd yield was recorded under subsurface placement of drip laterals at 15 cm depth but highest root length density was recorded under subsurface placement of drip laterals at 30 cm depth. The curd yield was increased by 5% under municipal wastewater irrigation with the saving of 28.3%, 21.1%, and 38.3% of Nitrogen, Phosphorus, and Potassium nutrients, respectively, over groundwater use. Significantly higher concentration of heavy metal elements Arsenic, Cupper, Chromium, Iron, Manganese, Lead, and Zinc was recorded by using municipal wastewater for irrigation over groundwater. However, concentration of all the heavy metals found in the curd of cauliflower was lower than their permissible limit as prescribed by the Food and Agriculture Organisation/World Health Organisation and Indian standards. This study provides an opportunity to utilize municipal wastewater through subsurface placement of drip laterals. It will protect our environment from wastewater pollution with the saving of inorganic fertilizers and fresh water that can be utilized in other priority sectors. Highlights: Subsurface drip at 15 cm depth given the highest curd yield of cauliflower. Higher root length density and leaf area index was observed under subsurface drip. Present study limits the heavy metal concentration in the food chain. Heavy metals concentration was lower than allowable limit as prescribed by standards.